A novel zirconium-based metal–organic framework covalently modified by methyl pyridinium bromide for mild and co-catalyst free conversion of CO2 to cyclic carbonates. Issue 3 (20th December 2022) - Xu, Jia-Hui; Peng, Shuai-Feng; Shi, Yu-Kun; Ding, Shan; Yang, Guang-Sheng; Yang, Yu-Qi; Xu, Yan-Hong; Jiang, Chun-Jie; Su, Zhong-Min
Abstract : (Br − )CH3 -Pyridinium-MOF-1 integrated reactive Lewis acid sites and Br − nucleophilic anions and exhibited efficient catalytic activity for the cycloaddition of CO2 to epoxides. Abstract : Building metal–organic frameworks (MOFs) covalently modified by onium halides is a promising approach to develop efficient MOF-based heterogeneous catalysts for the cycloaddition of CO2 to epoxides (CCE) into cyclic carbonates. Herein, we report a novel zirconium-based MOF covalently modified by methyl pyridinium bromide, Zr6 O4 (OH)4 (MPTDC)2.2 (N-CH3 -MPTDC)3.8 Br3.8 ((Br − )CH3 -Pyridinium-MOF-1 ), where MPTDC denotes 3-methyl-4-pyridin-4-yl-thieno[2, 3- b ] thiophene-2, 5-dicarboxylate. The structure and composition of this complex were fully characterized with PXRD, NMR, XPS, TEM and so on. CO2 adsorption experiments show that (Br − )CH3 -Pyridinium-MOF-1 has a higher affinity for CO2 than its electrically neutral precursor, which should be attributed to the fact that charging frameworks containing pyridinium salt have stronger polarization to CO2 . (Br − )CH3 -Pyridinium-MOF-1 integrated reactive Lewis acid sites and Br − nucleophilic anions and exhibited efficient catalytic activity for CCE under ambient pressure in the absence of co-catalysts and solvents. Furthermore, (Br − )CH3 -Pyridinium-MOF-1 was recycled after five successive cycles without substantial loss in catalytic activity. The corresponding reaction mechanism also was speculated.